Gambaran Kepositifan Basil Tahan Asam Pasien Diagnosis Klinis Tuberculosis Paru di Balai Kesehatan Masyarakat Semarang - Fitriani Kahar; Putri Anggraeni Novitasari; Irnawati Irnawati (Poltekkes Kemenkes Semarang, 2022)
Tuberculosis is an infectious disease caused by Mycobacterium tuberculosis. Until now, tuberculosis is still a public health problem in the world. Tuberculosis is a dangerous infectious disease, the healing process also takes a long time. Acid-fast bacilli examination is an examination to determine the presence or absence of Mycobacterium tuberculosis bacteria. The factors that influence Tuberculosis patients are age, gender, education and occupation. The purpose is to knowing the description of AFB positivity in patients with clinical diagnosis of pulmonary tuberculosis at Balkesmas Semarang in 2020. This research was an observational study with descriptive research criteria through a retrospective approach. Results from 656 patients with clinical diagnosis of tuberculosis who underwent acid-fast bacilli examination, 220 patients (33.5%) were found positive and acid-fast bacilli were negative (64.5%). The results of the examination of acid-fast bacilli were positive with a scanty positivity degree of 3 patients (1.4%), acid-fast bacilli (+1) were 71 patients (32.3%), (+2) were 83 patients (37.7%), (+3) as many as 63 patients (28.6%). Based on the category of age 0-14 years as many as 1 patient (0.5%), 15-34 years as many as 78 patients (35.5%), 35-54 years as many as 96 patients (43.6%), 55-74 years as many as 44 patients (20%), 75 years as many as 1 patient (0.5%). Based on gender, there were 123 patients (56%) male and 97 female patients (44%). Conclusion the results of the examination of acid-fast bacilli were positive with a scanty positivity rate of 3 patients (1.4%), acid-fast bacilli (+1) 71 patients (32.3%), (+2) 83 patients (37.7%), (+3) 63 patients (28.5%). Based on gender with positive acid-fast bacilli, there were 123 male patients (56%) while female 97 patients (44%). Age with the most positive acid-fast bacilli results in the range 0–14 years 1 patient (0.5%), 15–34 years 78 patients (35.5%), 35-54 years 96 patients (43.6%), 55 –74 years.